Pengaruh Faktor Sosial Dan Pribadi Terhadap Minat Beli Produk Peyek Aziz Tanpa Tanggal Kedaluwarsa Dalam Perspektif Ekonomi Syariah - Wiwi Mulyani; Ai Siti Khoeriah; Saepul Bahri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
Carrying out economic activities based on Islam is an order and has the value of worship. According to fiqh rules, every muammalah transaction is allowed as long as it does not conflict with the basic Islamic law, namely the Qur'an and hadith, including carrying out economic activities in the field of food processing business. The purpose of this study was to determine the influence of social factors and personal factors on consumer buying interest in Peyek Aziz products. The method used is descriptive quantitative with the number of samples used as many as 33 respondents in the Kertamukti sub-district, Campaka sub-district which was determined through probability sampling with random sampling technique. The results of this study indicate that personal factors affect consumer buying interest with a significance value of 0.000 < 0.05. Social factors are declared not to affect because the significance value obtained is 0.063 > 0.05. While social and personal factors jointly affect consumer buying interest with a significance value of 0.000 < 0.05. Based on these results, it is known that social and personal factors affect consumer buying interest in food without an expiration date of 0.515 or 51%. While the remaining 49% is influenced by other factors not examined. The sharia economic review regarding food without expired labels did not find any specific regulatory information. The inclusion of an expired label is an ijtihad in providing information on the appropriate time limit for consumption on food products with the aim of benefiting in maintaining property and life.